Emission Efficiency Enhancement of Er3+ Ions in Silica by Near‐Field Coupling With Plasmonic and Pre‐Plasmonic Nanostructures. Issue 3 (17th October 2017) - Kalinic, Boris; Cesca, Tiziana; Scian, Carlo; Michieli, Niccoló; Balasa, Ionut Gabriel; Trave, Enrico; Mattei, Giovanni
Abstract : Plasmonic nanostructures have been the object of strong scientific interest in the last decade for their linear and nonlinear optical properties. The present work is focused on the capability to control and enhance the Er 3+ emission efficiency in silica by near‐field coupling with plasmonic and pre‐plasmonic nanostructures. The results shows that more than one order of magnitude Er 3+ PL enhancement can be obtained with ultra‐small pre‐plasmonic Ag clusters synthesized by ion implantation and thermal annealing. Moreover, resonantly coupled extended plasmonic nanostructures in the form of gold nanohole arrays can efficiently interact with the Er ions, leading to a 20‐fold increase of their radiative emission at 1.54 μm. Abstract : The capability to control and enhance the Er 3+ emission efficiency in silica by near‐field coupling with plasmonic and pre‐plasmonic nanostructures is demonstrated . More than one order of magnitude Er 3+ PL enhancement is obtained with sub‐nanometric Ag clusters synthesized by ion implantation and thermal annealing. Moreover, resonantly coupled extended plasmonic nanostructures, as gold nanohole arrays, efficiently interact with the Er ions leading to a 20‐fold increase of their radiative emission at 1.54 µm.